An Individual Psychology Analysis of Main Character in the Freedom Writers Movie - Aulia, Agista Putri; Nurul Ismayanti, Safira; Nugroho, Abdillah (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2024)
Literary work is a creation of human based on reality and given the imagination through the media of speaking and writing. One of the examples of a literary work that can be used as learning is a film. Freedom Writers is a film directed by LaGravenese and released in 2007. This film tells the struggle of a young teacher who is determined and inspires students in his class at risk to learn tolerance. The purpose of this study is to analyze the creative power of the main character of the Freedom Writers film, namely Erin Gruwell, in solving the problems of students in her class using individual psychology theory by Alfred Adler. The problems faced are individual problems of these students, environmental problems, and problems that occur in private teachers. Creative power is individual freedom to make a change for the better. The method used in this research is qualitative research. Researchers used documentation to collect data from films. The data of this research is all utterances or dialogues concerning creative power uttered by Erin Gruwell. In analyzing the data, the researcher identified each scene that describes the creative power of Erin Gruwell's character by using the individual psychology theory by Alfred Adler. The results showed that there were five data including creative power which was carried out by Erin Gruwell.